SPE Asia Pacific Oil and Gas Conference and Exhibition 2002
DOI: 10.2118/77867-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Key Cement Additives on the Mechanical Properties of Normal Density Oil and Gas Well Cement Systems

Abstract: Recent advances in oil and gas cementing technology allow for the modeling and prediction of both compressive and tensile stresses upon an annular cement sheath, throughout the life of a well. Given the knowledge of the type and magnitude of stresses likely to be encountered in a specific location in a wells annulus gives designers target parameters for designing the mechanical properties necessary in the set cement to be able to sustain those stresses without failing. Such a mechanical failure in a cement she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Several previous studies suggested the use of different types of fibers such as the Wollastonite, organic, monofilament, and silicic fibers to improve properties of oil well cement at different conditions, the evaluated fibers were able to improve the strength (Shi et al 1995;Heinold et al 2002;Morris et al 2003;Iremonger et al 2015) and mitigate the loss circulation (Elmoneim et al 2000;Ilyas et al 2012;Al Maskary et al 2014;Arshad et al 2014) of the cement.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies suggested the use of different types of fibers such as the Wollastonite, organic, monofilament, and silicic fibers to improve properties of oil well cement at different conditions, the evaluated fibers were able to improve the strength (Shi et al 1995;Heinold et al 2002;Morris et al 2003;Iremonger et al 2015) and mitigate the loss circulation (Elmoneim et al 2000;Ilyas et al 2012;Al Maskary et al 2014;Arshad et al 2014) of the cement.…”
Section: Introductionmentioning
confidence: 99%
“…32−34 They can be very useful in controlling the hydration reactions of cement slurries due to their higher surface area. 35 These materials can enhance the compressive strength and integrity of the cement sheath, as well as control and reduce fluid losses from the cement slurries. 36,37 There are some applications reported in cement and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are used in the formulation of cement to increase its strength and durability. , Nanomaterials have a wide range of applications in different areas of petroleum engineering, such as exploration, drilling, and production. They have been used in other science fields such as biomedicines, electronics, polymer science, and catalysis . The application of nanotechnology in the field of oil well cementing can provide solutions to many problems related to integrity and durability of cement slurries. They can be very useful in controlling the hydration reactions of cement slurries due to their higher surface area . These materials can enhance the compressive strength and integrity of the cement sheath, as well as control and reduce fluid losses from the cement slurries. , There are some applications reported in cement and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…This study is primarily about lightweight cement slurries. Such cement systems, with densities in the range of 4–13.5 ppg, can be designed through nitrogen gas injection, , the addition of water extenders like bentonite and sodium silicate, or replacing proportions of cement with low-specific gravity materials, such as microspheres, fly ash, silica fume, and ground granulated blast furnace slag (GGBFS). , …”
Section: Introductionmentioning
confidence: 99%